Insect Community Status in Different Field Conditions and Clones in Kaliwining Cocoa Experimental Station, East Java, Indonesia: Sisko Budianto, Wiwin Windriyanti, Sri Wiyatiningsih, Indah Anitasari - Budianto, Sisko; Windriyanti, Wiwin; Wiyatiningsih, Sri; Sari, Indah Anita (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Insect communities are vital to the ecological and economic success of cocoa agroforestry systems, providing essential functions such in pollination, pest control, and nutrient cycling. Their presence and performance are shaped by field structure, clone genetics, habitat complexity, and agricultural practices. This research was conducted at the Experimental Station of the Indonesian Coffee and Cocoa Research Institute in Jember, East Java, which focused on two distinct types of cocoa fields (differences in planting years, plant density, and shade trees) and clones (clone ICCRI03, ICCRI09, and MCC02). The research highlights are the role of field conditions and genetic factors in shaping insect diversity and abundance. The trapping method used a yellow trap, and field conditions included plant height, canopy width, and leaf litter amount, which were measured. The observation revealed 35 insect morphospecies from 30 families and eight non- insect morphospecies, emphasizing the functional diversity of these communities. Field conditions and clones did not have a significant effect on insect abundance and diversity. Field conditions, including plant height, canopy width, and leaf litter amount, did not show a strong correlation with the abundance of insects. Field with more shade trees and vegetation, had a greater abundance of insects, notably predators and decomposers. MCC02 favored pollinator populations, ICCRI03 boosted predators and parasitoids, and ICCRI09 increased overall diversity. However, pollinators and omnivores showed minimal variety across fields and clones. Shannon diversity index values (H’ = 1.59-1.75) suggested moderate biodiversity with uneven species distribution. The study underscores the importance of main- taining habitat complexity, optimizing field management, and strategic clone selection to enhance ecosystem services like pollination and pest control while fostering biodiversity.